Sound visualization experiment using ultrasound - Lee, Zhi Xiong (2014)
The main objective of this Final Year Project is to research on methods to detect and image the edges of simple shaped objects using ultrasound. This research supplements the on-going project by Professor Yoon to develop a Biomimetic Acoustic Transducer (BAT) array to “determine the entire shape of topography in real time by characterizing the reflected acoustic wave collected by the BAT array”.